PENGARUH PROMOSI PENJUALAN DAN PERIKLANAN TERHADAP KEPUTUSAN PEMBELIAN TIKET PENERBANGAN PADA PT. PRIMA MEGAH WISATA MEDAN - Fredy, Fredy; Putra Limawan, Randy; Halim, Steven (Aksara Public, 2019)
Decreasing purchasing decisions can be seen from not achieving sales targets caused by sales and advertising promotion activities that have not attracted customers. The method used in this study is a quantitative approach, this type of research is quantitative descriptive, and the nature of this research is descriptive explanatory. The method of data collection is done by interviews, questionnaires, and documentation. The data analysis method used is multiple regression. The population is 134 customers and the sample in the study is 100 customers. Hypothesis calculation results The results of partial hypothesis calculations that the value of tcount (5.587) is greater t table (1,985) and a significant value of 0,000 is smaller than 0.05 and the tcount (2.666) is greater ttable (1,985) and a significant value of 0.009 is smaller than 0 , 05 while hypothesis testing simultaneously that the value of F count (19,729)> F table of (3,09) with a significance level of 0,000 <0,05. From these results that can be concluded simultaneously and partially sales and advertising promotions have a positive and significant effect on flight ticket purchase decisions at PT Prima Megah Wisata Medan. The magnitude of the coefficient of determination can be seen from the Adjusted R Square value of 0.274. This means that 27.4% of purchasing decisions can be explained by independent sales and advertising promotion variables while the remaining 72.6% is explained by other variables outside of this study, such as service quality, personal selling, prices and so on.